Medidas de mejoramiento efectivas aplicables a la infraestructura carretera del tramo Manzanillo-Melaque de la red carretera federal libre a partir de la evaluación con la metodología iRAP - Chávez Cerna, Gilberto (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
Currently, traffic accidents are major public health concern worldwide. According to the World Health Organization, each year 1.25 million people die worldwide due to traffic accidents. In Mexico, injuries caused by traffic remain among the top ten causes of death. In order to address this problem the United Nations (UN) declared 2011-2020 as the Decade of Action for Road Safety. A decade expected to strive on improving the road infrastructure, vehicle safety and user behavior on the roads. This issue of road safety will focus more on the road section of Manzanillo-Melaque, MEX-200 highway. It is considered one of great economic and social importance and it has reported serious problems in road accidents. In 2012, this section was evaluated by the International Program Road Assessment iRAP (International Road Assessment Program) as well as in 2015 by the innovative automated road system AMAC (Advanced Mobile Asset Collection). This research will be based on the results of both evaluations. The first methodology provides us with an investment plan for safer roads and a list of implementation measures requiring the stretch to improve road safety and the cost-benefit ratio of proposed improvement measures. The second provides information about the current state of the horizontal and vertical signage, pavement marking retroreflectivity, dimensions, location and placement angles, useful to develop maintenance programs, including traffic signals. Furthermore a data analysis of the road operation is presented to determine condition and functionality such as accidents, IRI, TDPA, vehicular decomposition, rut depth, macro texture and deterioration. Subsequently conducting a Road Safety Audit (RSA) is shown to accurately identify the road safety problems and gives rise to proposals for improvement measures that can be implemented to improve the road safety for all users. With all the information gathered and recommendations proposed by iRAP and AMAC a detailed intervention program is presented together with a particular 6 point identifier which analysis points of high risk (PdR) in the road in conjunction with activities to follow and counteract the problem.

En la actualidad los accidentes de tránsito son uno de los principales problemas de salud pública a nivel mundial. De acuerdo a cifras generadas por la Organización Mundial de la Salud cada año 1.25 millones de personas mueren en el mundo a causa de los accidentes de tránsito. En México, las lesiones causadas por el tránsito siguen encontrándose entre las diez principales causas de muerte. Con el fin de atender esta problemática la Organización de las Naciones Unidas (ONU) declaró el periodo 2011-2020 como el decenio de acción para la seguridad vial, década en la cual se espera que se lleven a cabo importantes esfuerzos para la mejora de la infraestructura vial, la seguridad de los vehículos y el comportamiento de los usuarios en las vías. En este trabajo se aborda el tema de la seguridad vial, el cual se enfoca al tramo carretero Manzanillo-Melaque de la carretera MEX-200, tramo considerado de gran importancia económica y social, que ha reportado en los últimos años problemas serios de siniestralidad. En el año 2012, dicho tramo fue evaluado con el Programa Internacional de Evaluación de Carreteras iRAP (International Road Assessment Programme) y, en el año 2015, fue evaluado con el sistema innovador de auscultación de carreteras AMAC (Advanced Mobile Asset Collection). Este trabajo parte de los resultados obtenidos en ambas evaluaciones. La primera metodología, nos proporciona un plan de inversión para vías más seguras y un listado de medidas de implementación que requiere el tramo para mejorar su seguridad vial, así como la relación costo-beneficio de las medidas de mejoramiento propuestas. La segunda, nos proporciona información respecto al estado actual del señalamiento horizontal y vertical, retroreflexión, dimensiones, ubicación y ángulos de colocación, es de gran utilidad para elaborar los programas de mantenimiento y conservación de las señales de tránsito.
Facultad de Ingeniería Civil. Maestría en Infraestructura del Transporte en la Rama de las Vías Terrestres
Keywords: info:eu-repo/classification/cti/7; FIC-M-2016-1348; IRI; ASV; AMAAC; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3035